2018
DOI: 10.1093/bioinformatics/bty435
|View full text |Cite
|
Sign up to set email alerts
|

TomoEED: fast edge-enhancing denoising of tomographic volumes

Abstract: Supplementary data are available at Bioinformatics online.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 9 publications
0
13
0
Order By: Relevance
“…This zone corresponds to the area previously displayed in the inset of Fig. 1 C. A) Oriented 20 nm-thick slice of a filtered reconstruction ( Moreno et al, 2018 ) in which densities are visible on both sides of the cellular and flagellar membranes. Cytoplasmic sticks of the FAZ filament (white arrows) are longer and more regularly arranged than the flagellar densities facing them (white arrowheads).…”
Section: Resultsmentioning
confidence: 76%
See 2 more Smart Citations
“…This zone corresponds to the area previously displayed in the inset of Fig. 1 C. A) Oriented 20 nm-thick slice of a filtered reconstruction ( Moreno et al, 2018 ) in which densities are visible on both sides of the cellular and flagellar membranes. Cytoplasmic sticks of the FAZ filament (white arrows) are longer and more regularly arranged than the flagellar densities facing them (white arrowheads).…”
Section: Resultsmentioning
confidence: 76%
“…S2 ). After denoising of the data using an edge-enhancing noise-reduction anisotropic diffusion filter ( Moreno et al, 2018 ), some short densities in the flagellar compartment are observed facing the cytoplasmic sticks ( Fig. 3 A, arrowheads).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The tomograms were binned 4 times to improve contrast prior to segmentation, thus the voxel size of the final segmentations was 1.684 nm (HeLa cell and mouse neuron) and 1.368 nm (yeast). The contrast of one tomogram of yeast (EMD-10767) was enhanced prior to segmentation using an anisotropic filter [ 58 ], while the contrast of the other tomogram of yeast (EMD-10765) and the one of the mouse neuron was enhanced using a deconvolution filter executed in MATLAB (MathWorks) using the functionalities of the TOM toolbox [ 59 ]. Membrane segmentations were generated automatically from tomograms using TomoSegMemTV [ 18 ] using parameters = 10 and = 0.3 (HeLa cell), = 12 and = 4 (yeast) and = 10 and = 3 (mouse neuron) and further refined manually using Amira Software ( ThermoFisher Scientific ).…”
Section: Methodsmentioning
confidence: 99%
“…XTEND data series were processed as described previously (28) using python scripts. Tomographic reconstructions were performed using TOMO3D software, 30 iterations of simultaneous iterative reconstruction technique (SIRT) algorithm (29) and edge enhanced using TOMOEED (30). Segmentation of volumes was carried out with SuRVoS (31), and volumes were represented with Chimera (32) and ImageJ (33).…”
Section: Methodsmentioning
confidence: 99%